Fatty Acid Profile, Carotenoid Content, and In Vitro Anticancer Activity of Karimunjawa and Lampung Sea Cucumber - Ekowati Chasanah; Yusro Nuri Fawzya; Kustiariyah Tarman; Hedi Indra Januar; Muhammad Nursid (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2016)
Fatty acids and carotenoid has been known as an anticancer agent on both preventing and treating cancer disease. This study was conducted to analyze the fatty acid profile, carotenoid and in vitro anticancer activity of 12 sea cucumber harvested from Karimunjawa and Lampung waters. The aim of the study was to determin the potency of sea cucumbers as raw material for nutraceutical products. Fatty acid profile and carotenoid content were characterized by gas chromatography and spectrophotometry techniques, while in vitro anticancer activity was assessed by MTT assay against cervix (HeLa), breast (T47D and MCF-7) and colon (WiDR) cancer cells. Results of the study showed polyunsaturated fatty acid (PUFA) dominated the composition of fatty acids in the samples from both locations. Holothuria sp. was detected to contain the highest amount of carotenoid. Furthermore, the highest in vitro anticancer activity was detected also in the sample of Holothuria sp. The activity of 30 ppm Holothuria sp. extract against HeLa cell was detected to be almost equal to the 5 ppm doxorubicin control. Concentration of 5 ppm Holothuria sp. extract also showed positive result in killing 50% of MCF-7 and T47D, but capable to 100% kill HeLa and WiDR cells. At concentration of 25 ppm, the extract was able to kill all the 4 cells tested. Statistical analysis showed the amount of carotenoid and two particular fatty acid compounds (docosadienoic and eicosapentaenoic acid) significantly (P0.05) contributed to the cytotoxic activity that was found in the sea cucumber samples. Those compounds were found in highest concentration from Holothuria sp harvested from Lampung waters, thus being the most prospective raw material for nutraceutical or functional food ingredient with anticancer potency.